ISSUES OF EDUCATION AND UPBRINGING IN THE SPIRITUAL HERITAGE OF NAVOI - Bekzod Baratbaev; Mohidil Muhiddinova (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper highlights the views of our great ancestors about the immortal cultural and spiritual heritage that affect the upbringing of the young generation. Namely, opinions are stated that in the work of the plaintiff the Uzbek literature writer A. Navoi, contains thoughts such as universal human dignity, the values of national customs and ideas, brief information on the philosophical reasoning of the poet is given, the topic of friendship, behavior and upbringing, and the harmonious development of personality are also touched upon.